2017
DOI: 10.1159/000485593
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid in the Follow-Up Determines 30% Decline in Estimated GFR Over 2 Years: a Propensity Score Analysis

Abstract: Background/Aims: Higher level of serum uric acid (SUA) predicts early entry to dialysis in chronic kidney disease (CKD) patients. However, a short-term effect of SUA remains to be elucidated using a novel surrogate endpoint. Methods: Japanese CKD stage 3 to 4 patients were retrospectively examined (n= 701). The follow-up level of SUA was estimated as timeaveraged uric acid (TA-UA). A propensity score for 6.0, 6.5 or 7.0 mg/dL of TA-UA was respectively calculated using baseline 23 covariates. The time-to-event … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(53 reference statements)
1
3
0
Order By: Relevance
“…Meanwhile, consistent with previous studies [4][5][6][7][8][9][10][11][12], we found that uric acid levels were negatively correlated with eGFR in all subjects. In the regression analysis, various potential confounders were added in sequential order, but the results revealed only a modest reduction effect (the regression coefficient changed from -0.20 to -0.22 after adjusting for a range of confounders), strengthening the notion of a relationship between uric acid and eGFR.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Meanwhile, consistent with previous studies [4][5][6][7][8][9][10][11][12], we found that uric acid levels were negatively correlated with eGFR in all subjects. In the regression analysis, various potential confounders were added in sequential order, but the results revealed only a modest reduction effect (the regression coefficient changed from -0.20 to -0.22 after adjusting for a range of confounders), strengthening the notion of a relationship between uric acid and eGFR.…”
Section: Discussionsupporting
confidence: 93%
“…The association between uric acid and kidney disease has been previously investigated. Numerous studies reported a positive association between the levels of circulating uric acid and the risk of CKD progression [4][5][6][7][8][9][10][11][12], but this was negated in other studies [13][14][15]. Observational studies experience residual problems of poorly measured or unmeasured confounding factors and reverse causality when the disease process has a long latency period.…”
Section: Introductionmentioning
confidence: 99%
“…In CKD and dialysis patients, the effects of serum TA-UA level on cardiovascular outcomes, mortality, and progression of kidney function remain controversial or unknown. A higher level of TA-UA is considered to be the risk factor of CKD progression [16][17][18]. In addition, only a few studies have explored the effect of serum TA-UA on mortality in dialysis patients, but the results are inconsistent [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The British Society for Rheumatology recommends a target below 5 mg/dL, while the European League Against Rheumatism and the American College of Rheumatology suggest a target below 6 mg/dL [ 17 ]. Early intervention for sUA less than 6.0 mg/dL is recommended for slowing CKD progression in Japan [ 18 ]. In China, the optimal sUA level target for reducing CKD risk in different disease states remains unclear.…”
Section: Introductionmentioning
confidence: 99%